2022
DOI: 10.3389/fnut.2022.786022
|View full text |Cite
|
Sign up to set email alerts
|

Infant Distress in a Food Delay Task Changes With Development and Predicts Amount Consumed

Abstract: ObjectiveEating behavior regulation emerges during early development and involves general self-regulation (emotional, behavioral), appetite regulation (homeostatic metabolic need) and appetite self-regulation (including both Bottom-Up Food Approach and Bottom-Up Food Avoidance and top-down purposeful self-control of eating). Limited research has investigated developmental trajectories of the regulation of eating behavior before the preschool years. The current study used a novel food delay task to assess infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The emotion regulation pathway suggests that infants who demonstrate better emotion regulation such as less distress or easier soothing may be less likely to experience their caregivers' use of food to soothe them, and thus may not make the connection to food as a way to soothe emotional distress over time (i.e., stress‐eating). One study used a task that indexed multiple aspects of self‐regulation relevant for food and eating in infants, including emotion regulation, homeostatic hunger, and food reward responsivity, and found that infant distress while waiting for food was associated with greater consumption after the waiting period had ended, and that the strength of this association increased with age, highlighting connections between emotion and eating regulation 197 . Another hypothesized mechanism is the “impulse‐control” pathway, in which it is theorized that infants and young children who demonstrate better self‐control around tempting foods will be at lower risk for obesity over time because they have developed the “skill” of resisting such foods.…”
Section: The Early Life Exposome: Exposures During Infancy and Early ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The emotion regulation pathway suggests that infants who demonstrate better emotion regulation such as less distress or easier soothing may be less likely to experience their caregivers' use of food to soothe them, and thus may not make the connection to food as a way to soothe emotional distress over time (i.e., stress‐eating). One study used a task that indexed multiple aspects of self‐regulation relevant for food and eating in infants, including emotion regulation, homeostatic hunger, and food reward responsivity, and found that infant distress while waiting for food was associated with greater consumption after the waiting period had ended, and that the strength of this association increased with age, highlighting connections between emotion and eating regulation 197 . Another hypothesized mechanism is the “impulse‐control” pathway, in which it is theorized that infants and young children who demonstrate better self‐control around tempting foods will be at lower risk for obesity over time because they have developed the “skill” of resisting such foods.…”
Section: The Early Life Exposome: Exposures During Infancy and Early ...mentioning
confidence: 99%
“…One study used a task that indexed multiple aspects of self-regulation relevant for food and eating in infants, including emotion regulation, homeostatic hunger, and food reward responsivity, and found that infant distress while waiting for food was associated with greater consumption after the waiting period had ended, and that the strength of this association increased with age, highlighting connections between emotion and eating regulation. 197 Another hypothesized mechanism is the "impulse-control" pathway, in which it is theorized that infants and young children who demonstrate better self-control around tempting foods will be at lower risk for obesity over time because they have developed the "skill" of resisting such foods. Modeling the interplay among aspects of selfregulation such as emotion regulation, food reward responsivity, and impulse control, in both lab-based and real-world contexts will be essential to make better predictions regarding obesity risk.…”
Section: Self-regulationmentioning
confidence: 99%